SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENYULUH PERTANIAN MENGGUNAKAN METODE ANALITYCHAL HIERARCHY PROCESS - Alter Lasarudin (Universitas Muhammadiyah Gorontalo, 2021)
This research was done in Implementing Agency for Agricultural Extension of Fisheries and Forestry Gorontalo City. This research purpose is to design and implementing a Decision Support System to determine agricultural extension agents at the Fishery and Forestry Extension Implementing Agency (BP4K) of Gorontalo City. Researcher will using a multicriteria support decision system named Analytical Hierarchy Process (AHP).With sub-criteria: credit score (K1), duration of promotion (K2), agricultural extension preparation activities (K3), Agricultural extension activities (K4), evaluation activities and agricultural extension reporting in the last 3 years (K5) agriculture in the last 3 years (K6), Professional development activities in the last 3 years (K7), Acquired awards / tandajasa (K8).Based on the results of processing with Analytical Hierarchy Process method is quite effective in accelerating the decision-making process by solving the problem into its parts.